Virulence factors and antimicrobial resistance in Staphylococcus aureus isolated from bovine mastitis in Brazil - Pérez, Verónica K. C. (Braz J Microbiol, 2020)
This study aimed to evaluate virulence factors and genetic markers of antimicrobial resistance in 400 Staphylococcus aureus strains isolated from bovine mastitis in four Brazilian states, as well as to assess the association between these characteristics and field information. Virulence factors and drug resistance genes were identified by PCR screening. Biofilm-forming and hemolytic phenotype were detected using Congo red Tryptic Soy Broth and defibrinated sheep blood agar, respectively. Of all isolates, 83.5% were biofilm-forming and 98.5% strains exhibited biofilm gene icaAD, and a significant association between phenotype and genotype for biofilm was observed (P = 0.0005). Hemolysin genes were observed in 82.85% (hla(+)hlb(+)), 16.5% (hla(+)) and 0.75% (hlb(+)) isolates, whereas the hemolytic phenotype exhibited was complete and incomplete hemolysis in 64.25%, complete in 28.25%, incomplete in 4.75%, and negative in 2.75% of the strains. Virulence factors genes luk, seb, sec, sed, and tst were observed in 3.5%, 0.5%, 1%, 0.25%, and 0.74% isolates, respectively. The gene blaZ was detected in 82.03% of penicillin-resistant isolates, whereas tetK and aac(6′)-Ie–aph(2′)-Ia were observed in 33.87% and 45.15% of the tetracycline and aminoglycosides-resistant isolates, respectively. Fluoroquinolone resistance gene mepA was detected for the first time in S. aureus from bovine mastitis. Resistance genes tetM (3.22%), tetL (1.61%), ermA (14.29%), ermB (14.29%), ermC (33.3%), ermT (9.52%), ermY (4.76%), msrA (9.52%), and mphC (9.52%) were also detected among resistant isolates. No association between virulence factors or antimicrobial-resistant genes and year of isolation, geographic origin, or antimicrobial resistance profile was observed. Our results showed that S. aureus strains isolated from bovine mastitis in the four Brazilian states sampled are mainly biofilm-forming and hemolytic, whereas virulence genes associated with enterotoxins, luk and tst, were less frequently observed. Moreover, a wide variety of resistance genes that confer resistance to almost all classes of antimicrobial agents approved for use in animals and humans were found. Overall, the data point to a great pathogenic potential of S. aureus associated with bovine mastitis and to the non-negligible risks to public health of staphylococcal infections from animal origin. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s42770-020-00363-5) contains supplementary material, which is available to authorized users.